State supervision in the People’s Republic of China - ZAKHARENKOVA, VERA V. (The journal of contemporary issues in business and government, 2021)
The choice of this topic was due to the desire of the author to highlight some of the provisions of the PRC Law "On Supervision", the provisions of the Constitution of the PRC regarding the creation of a state supervisory authority. The author touches upon the theme of the reform of the state supervision system, the purpose of which is to pool resources for fighting corruption, creating unified and effective state control with Chinese characteristics. The article also presents the amendments to the Criminal Procedure Code of the People's Republic of China, which took place in October 2018, among which it is said about the improvement of the mechanism of supervision in connection with the adoption of the Law of the People's Republic of China “On Supervision”. In this paper, the author examines in detail the authority, composition, and responsibilities of the highest supervisory authority of the PRC - the National Supervisory Committee of the PRC (NSC). The article lists the officials who are supervised by the supervisory authority under the Law of the People's Republic of China “On Supervision”. Special attention is paid to the detention of a person by the organs of the National Supervisory Committee of People's Republic of China, as a measure restricting the freedom of the individual. In the course of writing the work, the author concludes that the creation of a state supervisory authority was a great achievement for the PRC regarding the fight against corruption crimes.